2018
DOI: 10.1021/acs.est.8b01792
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Measurements of Nitric Oxide, Nitrogen Dioxide, and Nitrous Acid in an Occupied New York Home

Abstract: Indoor oxidizing capacity in occupied residences is poorly understood. We made simultaneous continuous time-resolved measurements of ozone (O), nitric oxide (NO), nitrogen dioxide (NO), and nitrous acid (HONO) for two months in an occupied detached home with gas appliances in Syracuse, NY. Indoor NO and HONO mixing ratios were higher than those outdoors, whereas O was much lower (sub-ppbv) indoors. Cooking led to peak NO, NO, and HONO levels 20-100 times greater than background levels; HONO mixing ratios of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(167 citation statements)
references
References 74 publications
11
155
1
Order By: Relevance
“…containing species that could be trapped and form nitrite in residual amounts on the 178 denuders, especially NO 2 . Our method development study showed NO 2 tends to absorb in 179 the same amount (difference <4%) on the walls of each denuder in a train setup, which is 180 consistent with other studies (Perrino et al, 1990;Zhou et al, 2018). On the basis of this 181 validation, the second denuder extract is used to correct the first denuder extract for both 182 concentration and isotopic composition .…”
supporting
confidence: 78%
“…containing species that could be trapped and form nitrite in residual amounts on the 178 denuders, especially NO 2 . Our method development study showed NO 2 tends to absorb in 179 the same amount (difference <4%) on the walls of each denuder in a train setup, which is 180 consistent with other studies (Perrino et al, 1990;Zhou et al, 2018). On the basis of this 181 validation, the second denuder extract is used to correct the first denuder extract for both 182 concentration and isotopic composition .…”
supporting
confidence: 78%
“…The range of photolysis rate constants due to indoor illumination sources ranges from very small for LEDs to 1.3 × 10 −5 /s 1 m from a bare fluorescent bulb . A typical indoor HONO concentration is about 5‐10 ppb but can rise as high as 50 ppb during cooking . HONO photolysis raises the OH concentration by 3 × 10 4 molec/(cm 2 s), 1 m from a fluorescent bulb with a background HONO mixing ratio of 5 ppb.…”
Section: Resultsmentioning
confidence: 99%
“…Indoors, background levels of HONO may persist due to equilibrium between the gas‐phase and reservoirs on indoor surfaces . Higher HONO levels are caused by indoor combustion activities such as cooking with a gas stove . The indoor photolysis rate constant of HONO ( J ) under attenuated sunlight has been measured to be 1.26 × 10 −4 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The indoor photolysis rate constant of HONO ( J ) under attenuated sunlight has been measured to be 1.26 × 10 −4 s −1 . Using indoor HONO measurements from Zhou et al . and the AER and assumed photolysis distributions described in Table , the distribution describing the total effective emission rate of HONO ([ E / V ] HONO , due to the combined time‐averaged processes of combustion and background evaporation from surfaces) was generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation